How will anthropology cope with the challenges of a changing world? - Oliven,Ruben George (2019)
Abstract The world has gone through many changes since the beginning of Anthropology and during the current century we will see many other changes that are impossible to predict. This article discusses what sort of theories and methodologies Anthropology will have to develop in order to understand what is going on in the world today. One of the challenges of Anthropology will be both to remain committed to rights of the groups that represent cultural diversity and to the theoretical task of offering interpretations of the social phenomena with which the world is faced.